2019
DOI: 10.1021/acs.jpcc.9b00297
|View full text |Cite
|
Sign up to set email alerts
|

Dye Encapsulation in Fluorescent Core–Shell Silica Nanoparticles as Probed by Fluorescence Correlation Spectroscopy

Abstract: Synthetic advances in the formation of ultrasmall (<10 nm) fluorescent poly(ethylene glycol)-coated (PEGylated) core-shell silica nanoparticles (SNPs), enabling improved particle size and surface chemical property control have led to successful clinical translation of SNPs as diagnostic probes in oncology. Despite the success of such probes, details of the dye incorporation and resulting silica architecture are still poorly understood. Here, we employ afterpulse-corrected fluorescence correlation spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 68 publications
1
40
0
Order By: Relevance
“…This effect has been quantitatively analyzed in earlier static and dynamic spectroscopy studies and is due to an increase in radiative rate and decrease in non‐radiative rate. [ 30–32 ] As shown previously, this brightness enhancement relative to free dye carries over into photon emission enhancements during dye blinking, which is crucial for a potential probe for STORM for which localization precision is proportional to the square root of brightness. [ 4–6 ] Confocal fluorescence correlation spectroscopy (FCS) measurements on the diffusing PEG‐Cy5‐aC’ dots yielded one‐component autocorrelation functions (ACF) suggesting an average particle diameter of 4.6 nm and corroborating the narrow size dispersity reflected in the TEM results (Figure 1d).…”
Section: Figurementioning
confidence: 94%
See 1 more Smart Citation
“…This effect has been quantitatively analyzed in earlier static and dynamic spectroscopy studies and is due to an increase in radiative rate and decrease in non‐radiative rate. [ 30–32 ] As shown previously, this brightness enhancement relative to free dye carries over into photon emission enhancements during dye blinking, which is crucial for a potential probe for STORM for which localization precision is proportional to the square root of brightness. [ 4–6 ] Confocal fluorescence correlation spectroscopy (FCS) measurements on the diffusing PEG‐Cy5‐aC’ dots yielded one‐component autocorrelation functions (ACF) suggesting an average particle diameter of 4.6 nm and corroborating the narrow size dispersity reflected in the TEM results (Figure 1d).…”
Section: Figurementioning
confidence: 94%
“…We determined an average of 2.5 Cy5 dyes per particle from the combination of FCS derived sample concentration and absorption spectroscopy results. [ 30,32 ] Furthermore, photobleaching studies based on previously published methods (see Supporting Information) showed that Cy5 encapsulated in aC’ dots is 2.8 times more photostable than in free form (Figure 1e). [ 33 ] Since we already showed in two separate previous studies that Al is fourfold coordinated in aC’ dots, replacing Si in the silica network, we did not repeat the same solid‐state 27 Al nuclear magnetic resonance (NMR) spectroscopy experiments on aC’ dot samples here.…”
Section: Figurementioning
confidence: 99%
“…The resulting reaction solution of C' dots was purified by centrifuging with a 30K MWCO PES membrane spin filter, and finally by GPC purification through Superdex 200 resin on a Bio-Rad fast protein liquid chromatography. The purified particles were characterized using fluorescence correlation spectroscopy (FCS) on a home-built setup, equipped with a 633-nm solid-state laser as the excitation source for Cy5(þ) dye, and UV/Vis spectroscopy on a Cary 5000 spectrometer as described previously (43,49). TEM images were taken using a FEI Tecnai T12 Spirit microscope operated at an acceleration voltage of 120 kV.…”
Section: Synthesis Of Azido-dpeg 8 -Phe-lys-pabc-apdmg Drug-linkermentioning
confidence: 99%
“…As-synthesized DFO-Gef-C' dots were then subjected to morphology, size, and surface payload density characterizations using a combination of transmission electron microscopy (TEM), fluorescence correlation spectroscopy (FCS), and UV/Vis spectroscopy. The hydrodynamic particle size, particle brightness, and concentration were obtained by fitting the FCS autocorrelation curves (43,49). The number of Cy5 dyes (or functional groups of DFO, DBCO) per DFO-Gef-C' dot was calculated using a similar method we reported previously (43,49).…”
Section: Synthesis and Characterization Of Dfo-mentioning
confidence: 99%
See 1 more Smart Citation